The diagnostic value of Soluble ST2, MIC-1 and NLR in pulmonary hypertension associated with chronic obstructive pulmonary disease: Soluble ST2, MIC-1 and NLR in COPD - Chen, Wei; Lyu, Guoling; Shi, Qinghua; Li, Xubin; Li, Xinyu; Huang, Yurong (Journal of Medical Biochemistry, 2026)
[Objective] To explore the diagnostic efficacy of serum soluble tumorigenic factor-2 (Soluble ST2), Macrophage Inhibitory Cytokine-1 (MIC-1), and neutrophil/lymphocyte ratio (NLR) for the poor prognosis of pulmonary hypertension (PH) associated with chronic obstructive pulmonary disease (COPD). [Methods] The COPD mixed with PH group consisted of 242 patients who received a diagnosis of COPD combined with PH at our hospital between January 2023 and December 2024. Patients with COPD and PH were further separated into two groups: those with a fair prognosis (186 patients) and those with a bad prognosis (56 patients). 90 healthy people who had physical examinations were chosen as the healthy control group, and another 150 patients with uncomplicated COPD within the same time period were chosen as the COPD group. Multivariate analysis of the effects of serum Soluble ST2 and MIC-1 levels and the NLR on the prognosis of COPD combined with PH in each group, the relationships between serum Soluble ST2 and MIC-1 levels and the NLR and the severity of COPD combined with PH, and the diagnostic value of COPD combined with PH for poor prognosis. [Results] The COPD combined with PH group’s serum Soluble ST2, MIC-1, and NLR levels were noticeably higher. Compared with the healthy control group, the COPD group presented significantly greater differences (P<0.05), which increased with increasing severity of PH. The group with a good prognosis had a considerably higher level of left ventricular ejection fraction (LVEF) than the group with a poor prognosis, whereas the levels of serum Soluble ST2, MIC-1 and NLR in the poor prognosis group were significantly greater than those in the good prognosis group, and the differences were statistically significant (P<0.05). There were no statistically significant differences in age, sex, disease duration, hypertension status, diabetes status, triglyceride, cholesterol, high-density lipoprotein or low-density lipoprotein levels (P>0.05). [Conclusion] The levels of serum Soluble ST2 and MIC-1 and the NLR are indicators reflecting the severity of COPD combined with PH. The combined detection of these three indicators is helpful for improving the diagnostic efficacy for the poor prognosis of patients with COPD combined with PH.